322 THORACOSCOPIC RETROSTERNAL GASTRIC CONDUIT RESECTION IN THE SUPINE POSITION FOR GASTRIC TUBE CANCER. (17th September 2021) - Horie, Kazumasa; Oshikiri, Taro; Horikawa, Manabu; Kitamura, Yu; Takiguchi, Gosuke; Urakawa, Naoki; Hasegawa, Hiroshi; Yamamoto, Masashi; Kanaji, Shingo; Matsuda, Yoshiko; Yamashita, Kimihiro; Matsuda, Takeru; et al.
Abstract: : Recent advances in treatment for esophageal cancer have improved prognosis after esophagectomy, but they have led to an increased incidence of gastric conduit cancer. In most gastric conduit cancer patients who underwent retrosternal reconstruction, median sternotomy is performed, which is associated with a risk of postoperative bleeding and osteomyelitis; pain often negatively affects respiration. To avoid these problems, we developed thoracoscopic retrosternal gastric conduit resection in the supine position (TRGR-S) as new procedure. Methods: We performed the first case of TRGR-S for a 75-year-old male with retrosternal gastric conduit cancer. He was placed in the supine position. Four ports were placed in the left chest wall. The gastric conduit was separated from the epicardium, sternum, and left brachiocephalic vein. Due to adhesions between the gastric tube and the right pleura, combined resection of the right pleura was performed. Next, pediculated jejunal reconstruction via the presternal route was performed. Results: Because there were few adhesions in the left thoracic cavity, this approach provided safety and a good surgical view, and it was easy to recognize the landmark including epicardium, sternum, and left brachiocephalic vein leading to appropriate resection of the tissue. Furthermore, there were few restrictions on the operative angle for the forceps and operability was quite ergonomic. Moreover, the lungs can be noninvasively contracted via an artificial pneumothorax. The pathological diagnosis was signet ring cell carcinoma (pT1b, pN0, M0, pStage I), indicating R0 resection. There were no post-operative complications. Conclusion: This approach does not require sternotomy, so it has less risk of postoperative bleeding and osteomyelitis. Due to fewer adhesions, this approach is safe and provides a good surgical view. TRGR-S is a safe, ergonomic, and reliable procedure for resection of retrosternal gastric conduit cancer. Video: This is the video of the operation 'TRGR-S', which is the new procedure for the gastric conduit cancer. https://www.dropbox.com/s/2whnekgp73hw1lz/video%20for%20ISDE2020.mov?dl=0 .